Engineering Identities, Epistemologies and Values: Engineering Education and Practice in Context, Volume 2 - Christensen, S.H (Springer, 2015)
This second companion volume on engineering studies considers engineering practice including contextual analyses of engineering identity, epistemologies and values. Key overlapping questions examine such issues as an engineering identity, engineering self-understandings enacted in the professional world, distinctive characters of engineering knowledge and how engineering science and engineering design interact in practice.